1996
DOI: 10.1097/00005392-199610000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Improved Management of Abdominal Undescended Testicular Tumors with Bulky Confluent Retroperitoneal Nodal Metastases

Abstract: Surgical removal of the primary tumor in an undescended testis with bulky metastasis is difficult. We believe that initial chemotherapy followed by 1-stage surgical removal of the primary and residual metastasis is a favorable option to improve compliance and decrease the incidence of loss to followup. Atypically altered ilioinguinal metastases may necessitate a change in radiotherapy ports and/or retroperitoneal lymph node dissection boundaries. The significantly poorer survival with nonseminomatous germ cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Kulkarni et al [3] reported 10 patients with nonseminomatous tumours; six of these were disease‐free after initial chemotherapy and the others underwent a one‐stage surgical removal of the primary and residual metastases [3]. Adjuvant chemotherapy was given to those with active tumour [3]. The present case is exceptional as a large‐volume mixed germ cell tumour appeared to have arisen within an intra‐abdominal testis late after apparent orchidectomy for an abdominal testis.…”
Section: Commentmentioning
confidence: 98%
See 3 more Smart Citations
“…Kulkarni et al [3] reported 10 patients with nonseminomatous tumours; six of these were disease‐free after initial chemotherapy and the others underwent a one‐stage surgical removal of the primary and residual metastases [3]. Adjuvant chemotherapy was given to those with active tumour [3]. The present case is exceptional as a large‐volume mixed germ cell tumour appeared to have arisen within an intra‐abdominal testis late after apparent orchidectomy for an abdominal testis.…”
Section: Commentmentioning
confidence: 98%
“…Undescended testes are 35±48 times more likely to undergo malignant change than a normal testis, and < 10% of testicular tumours occur within an undescended testis [2]. In adults with uncorrected intra-abdominal testes nonseminomatous germ cell tumours are less common than pure seminomas [3]. Kulkarni et al [3] reported …”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations